2013
DOI: 10.1021/jp401923v
|View full text |Cite
|
Sign up to set email alerts
|

Selective Dynamic CO2 Separations on Mg-MOF-74 at Low Pressures: A Detailed Comparison with 13X

Abstract: This study investigates the potential of the well-known metal− organic framework (MOF) Mg-MOF-74 for low-pressure CO 2 separations under dynamic conditions. We developed a technique to make pellets of Mg-MOF-74 without large capacity loss and measured CO 2 and CH 4 isotherms on these pellets up to 40 bar in the temperature range of 293−338 K. Dynamic breakthrough separation experiments with mixtures of CO 2 and CH 4 on a column packed with Mg-MOF-74 pellets at 308 K and 1 bar indicated a higher CO 2 capacity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 55 publications
(101 reference statements)
2
67
0
Order By: Relevance
“…[ 47,48 ] During this new experiment a column was packed with pelletized sample, which was then purged with an inert gas (e.g., He) to remove any water or other adsorbed species. The sample was then exposed to a stream of gaseous mixture, such as 15% CO 2 with 85% N 2 .…”
Section: Metal-organic Framework (Mofs)mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 47,48 ] During this new experiment a column was packed with pelletized sample, which was then purged with an inert gas (e.g., He) to remove any water or other adsorbed species. The sample was then exposed to a stream of gaseous mixture, such as 15% CO 2 with 85% N 2 .…”
Section: Metal-organic Framework (Mofs)mentioning
confidence: 99%
“…For example, Remy et al have reported that the performance of Mg-MOF-74 decreased upon the cycling of humid CO 2 in a linear manner as the number of cycles increased, a result that could have important ramifi cations for the suitability of Mg-MOF-74 as a potential CCS adsorbent. [ 48 ] Another selectivity study has also been carried out by collating data from many reports on using MOF systems for CO 2 specifi c adsorption. [ 41 ] During separation of CO 2 from the fl ue gas stream using a vacuum-swing adsorption (VSA) regeneration process, MOFs were also found to be less effi cient than zeolites.…”
Section: Metal-organic Framework (Mofs)mentioning
confidence: 99%
“…N 2 , CO 2 ) deteriorates significantly upon exposure to water vapor. [28][29][30][31][32] Upon hydration, gas sorption measurements show that MOF-74 compounds lose a substantial fraction of their original gas uptake capacity (N 2 , CO 2 ) even at 9% relative humidity and with subsequent thermal regeneration to remove adsorbed water molecules. These results point to an irreversible reaction within MOF-74, but X-ray diffraction measurements and infrared spectroscopy have not been able to detect a notable structural change or chemical transformation following hydration and thermal regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The magnesium based Mg-MOF-74 has demonstrated the highest CO2 uptake at low to moderate pressures of any solid adsorbent 23 . Mg-MOF-74 powder has been used to remove CO2 selectively from flue gas (N2) streams 24,25 and separate CO2/CH4 mixtures [26][27][28] via adsorption. However, research into the fabrication of M-MOF-74 membranes is so far limited.…”
Section: Introductionmentioning
confidence: 99%